Photodynamic therapy in Pythium insidiosum - an in vitro study of the correlation of sensitizer localization and cell death. - Layla Pires; Sandra de Moraes Gimenes Bosco; Maurício S Baptista; Cristina Kurachi (PLoS ONE, 2014)
Pythiosis is an infectious disease caused by Pythium insidiosum, a fungus-like organism. Due to the lack of ergosterol on its cell membrane, antibiotic therapy is ineffective. The conventional treatment is surgery, but lesion recurrence is frequent, requiring several resections or limb amputation. Photodynamic therapy uses photo-activation of drugs and has the potential to be an attractive alternative option. The in vitro PDT response on the growing of Pythium insidiosum culture was investigated using three distinct photosensitizers: methylene blue, Photogem, and Photodithazine. The photosensitizer distribution in cell structures and the PDT response for incubation times of 30, 60, and 120 minutes were evaluated. Methylene blue did not penetrate in the pathogen's cell and consequently there was no PDT inactivation. Photogem showed heterogenous distribution in the hyphal structure with small concentration inside the cells. Porphyrin-PDT response was heterogenous, death and live cells were observed in the treated culture. After 48 hours, hyphae regrowth was observed. Photodithazine showed more homogenous distribution inside the cell and with the specific intracellular localization dependent on incubation time. Photodithazine first accumulates in intracellular vacuoles, and at incubation times of one hour, it is located at all cell membranes. Higher inhibition of the growing rates was achieved with Photodithazine -PDT, over 98%. Our results showed that the photosensitizers that cross more efficiently the Pythium insidiosum membranes are able to cause extensive damage to the organism under illumination and therefore, are the best options for clinical treatment.